Belonging, Detachment and the Representation of Musical Identities in Visual Culture - Baldassarre, Antonio (Hollitzer Verlag, 2023)
Belonging, Detachment and the Representation of Musical Identities in Visual Culture is a volume of 28 essays exploring aspects of identity/ies in the field of music in visual culture.It is dedicated to the memory of Dorothea Baumann (1946-2022), an energetic champion of music iconographic research. Organised in six sections, the book explores theory and methodology; notation, intertextuality and interarts dialogue; and topics traversing courtly and ecclesiastical life, the fabrication and mechanism of cultural identity, colonialism, subversion and struggle.